Interventions among Child and Adolescent Inmates with Anxiety: A Literature Review - Nur Oktavia Hidayati; Dissy Lizara Diana; Indriyani Sari Astuti; Mega Mey Herviyanti; Syifa Ratna Kamila (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: This literature review aims to determine interventions among child and adolescent inmates with anxiety. Methods: The searching method used search engines such as google scholar and databases, such as Clinical Key, EBSCO and PubMed. Inclusion criteria for this literature review were Indonesian or English, published within the last 10 years and the research population must be child and adolescent inmates. Results: The results of the literature review showed that there were various interventions that can be done to overcome anxiety in child and adolescent inmates, including: Expressive Writing Therapy, Cognitive Behavioral and Family Psychoeducation Therapy, Logo and Supportive Therapy, Meditation, Art Therapy, and Supportive Therapy. Conclusions: Health workers, especially nurses, can use and combine various anxiety intervention options to help overcome anxiety in child and adolescent inmates according to the needs and conditions of the client.